(3dhGeY GdCacGQ GdeVjI aj TQM NeS GdeGA GdhQbi hGdCQV GdfLejIs - (3Ydj Hf eMeO Hf CjOeQ GdLdOcqj , YR GdOjf J (B742 (3g` s; (3eMeO Hf Gejd Hf YHO Gddg Hf Gejd (B( (3GSO (B)(3GdJejej,J (B170 (3g` s ((3CMeO Hf eMeO GHf abjQI s)
(3ChdgG (B:s
(3GdMeO ddg GdeHJOY HMceJg YLGFH GdeNdhbGJ CeG HYO aEf CNVd eG QZHJ ajg Gdgee GdRcjI GdadRGJ s
(3BNQgG (B:s
(3hdjcf BNQ eG bUOfGg ef TQM bUjOI Hf Cejd hGdMeO ddg QH GdYGdejf s
(3Cdag GdeDda SfI (B741 (3HOeTbs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdcjejGA h GdWHjYjGJs